Conductive member and solid oxide fuel cell comprising same
By using a three-dimensional mesh-like NiCrAl or NiCrAlFe metal porous body conductive member whose first main surface contains carbon atoms, the problem of increased contact resistance in a solid oxide fuel cell is solved, and stable output performance is achieved.
Patent Information
- Application Number
- CN202380066687.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-06-15
- Publication Date
- 2025-04-25
AI Technical Summary
In a solid oxide fuel cell, when the surface of the conductive member comes into contact with the connecting member, metal oxidation occurs as it is used, forming oxides, resulting in an increase in contact resistance and a decrease in output performance.
NiCrAl or NiCrAlFe metal porous body having a three-dimensional mesh structure skeleton is used as the conductive member, and its first main surface contains carbon atoms to suppress an increase in contact resistance.
The contact resistance between the conductive member and the connecting member during the use of the solid oxide fuel cell is effectively suppressed, and excellent output performance is maintained.
Smart Images

Figure CN119895597A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive member and a solid oxide fuel cell including the same. This application claims priority to Japanese Patent Application No. 2022-155329 filed on September 28, 2022, and all the contents described in the above Japanese Patent Application are cited. Background Art
[0002] Conventionally, a conductive member having a porous body containing nickel, chromium, and aluminum or a porous body containing nickel, chromium, iron, and aluminum has been used for a solid oxide fuel cell (Patent Document 1, Patent Document 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: International Publication No. 2016 / 021988;
[0006] Patent document 2: Japanese Patent Application Laid-Open No. 6-29024. Summary of the invention
[0007] An electrically conductive member according to one embodiment of the present invention comprises a porous body having a skeleton of a three-dimensional network structure.
[0008] The porous body is in the shape of a plate having a first main surface and a second main surface opposite to the first main surface.
[0009] The first main surface comprises carbon atoms,
[0010] The porous body is a NiCrAl metal porous body or a NiCrAlFe metal porous body.
[0011] A solid oxide fuel cell according to one embodiment of the present invention includes the above-mentioned conductive member. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic cross-sectional view showing an example of a conductive member according to one embodiment of the present invention.
[0013] Figure 2 yes Figure 1 Schematic enlargement of region II.
[0014] Figure 3 yes Figure 2 Schematic enlargement of region III.
[0015] Figure 4 yes Figure 1 Schematic enlargement of region IV.
[0016] Figure 5This is a schematic cross-sectional view showing an example of a solid oxide fuel cell according to an embodiment.
[0017] Figure 6 It is a schematic diagram which shows the method of measuring the value of contact resistance. DETAILED DESCRIPTION
[0018] [Problems to be Solved by the Invention]
[0019] In a solid oxide fuel cell, the surface of the conductive member is in contact with a connecting member (connector). In the surface region of the conductive member having a porous body containing nickel, chromium and aluminum or a porous body containing nickel, chromium, iron and aluminum, oxidation of the metal occurs with use to form oxides. Due to the generation of oxides, the contact resistance between the conductive member and the connecting member (connector) sometimes increases, and the output decreases.
[0020] An object of the present invention is to provide a conductive component which, when used in a solid oxide fuel cell, suppresses the increase in contact resistance accompanying the use of the solid oxide fuel cell. Another object of the present invention is to provide a solid oxide fuel cell whose output performance reduction is suppressed and has excellent output performance.
[0021] [Effects of the Invention]
[0022] According to the present invention, it is possible to provide a conductive member that suppresses an increase in contact resistance accompanying use of a solid oxide fuel cell when used in a solid oxide fuel cell, and a solid oxide fuel cell having excellent output performance while suppressing a decrease in output performance.
[0023] [Description of Embodiments of the Invention]
[0024] First, embodiments of the present invention will be listed and described.
[0025] [1] An electrically conductive member according to one embodiment of the present invention comprises a porous body having a skeleton of a three-dimensional network structure,
[0026] The porous body is in the shape of a plate having a first main surface and a second main surface opposite to the first main surface.
[0027] The first main surface comprises carbon atoms,
[0028] The porous body is a NiCrAl metal porous body or a NiCrAlFe metal porous body.
[0029] When used in a solid oxide fuel cell, the conductive member of one embodiment of the present invention suppresses the increase in contact resistance during use of the solid oxide fuel cell. Therefore, the solid oxide fuel cell having the conductive member can suppress the decrease in output performance and has excellent output performance.
[0030] [2] In the above [1], the carbon atoms may be present in the form of conductive carbon. When the conductive component of one embodiment of the present invention is used in a solid oxide fuel cell, the contact resistance is suppressed from increasing as the solid oxide fuel cell is used. Therefore, the solid oxide fuel cell having the conductive component can suppress the decrease in output performance and has excellent output performance.
[0031] [3] In the above [1] or [2], the skeleton may have a first region,
[0032] The first region is a region from the first main surface to a plane parallel to the first main surface, and the distance from the first main surface to the plane may be 10 nm.
[0033] The content of carbon atoms in the first region may be 10 atm% or more and 90 atm% or less. Thus, when the conductive component of one embodiment of the present invention is used in a solid oxide fuel cell, the contact resistance can be suppressed to a lower level. Therefore, the reduction in output performance of the solid oxide fuel cell having the conductive component can be further suppressed and has a more excellent output performance.
[0034] [4] In the above [3], the content may be 20 atm% or more and 80 atm% or less. When the conductive component of one embodiment of the present invention is used in a solid oxide fuel cell, the contact resistance is suppressed from increasing as the solid oxide fuel cell is used. Therefore, the solid oxide fuel cell having the conductive component can suppress the decrease in output performance and has excellent output performance.
[0035] [5] In the above [3], the content may be 30 atm% or more and 70 atm% or less. When the conductive component of one embodiment of the present invention is used in a solid oxide fuel cell, the contact resistance is suppressed from increasing as the solid oxide fuel cell is used. Therefore, the solid oxide fuel cell having the conductive component can suppress the decrease in output performance and has excellent output performance.
[0036] [6] In any one of [1] to [5] above, the thickness of the porous body may be 0.2 mm or more and 2 mm or less. The conductive component of one embodiment of the present invention has both strength and good conductivity. Therefore, a solid oxide fuel cell having the conductive component can have excellent output performance.
[0037] [7] In any one of [1] to [6] above, the average pore size of the porous body may be 60 μm or more and 3500 μm or less. The conductive component of one embodiment of the present invention has both good conductivity and air permeability. Therefore, a solid oxide fuel cell having the conductive component can have excellent output performance.
[0038] [8] In the above [7], the average pore size of the porous body may be 100 μm or more and 850 μm or less. The conductive component of one embodiment of the present invention has both good conductivity and air permeability. Therefore, the solid oxide fuel cell having the conductive component can have excellent output performance.
[0039] [9] In any one of [1] to [8] above, the average porosity of the porous body may be 50% or more and 98% or less. The conductive component of one embodiment of the present invention has both good strength and lightness. Therefore, a solid oxide fuel cell having the conductive component can have excellent strength and lightness.
[0040]
[10] In any one of [1] to [9] above, in the NiCrAl porous metal body, the skeleton body may contain a total of 55% by mass or more of Ni, Cr and Al. The conductive component of one embodiment of the present invention has excellent corrosion resistance and heat resistance. When used in a solid oxide fuel cell, the increase in resistance is suppressed. Therefore, the reduction in output performance of a solid oxide fuel cell having a conductive component can be suppressed and has excellent output performance.
[0041]
[11] In any one of [1] to [9] above, in the NiCrAlFe metal porous body, the skeleton body may contain a total of 55% by mass or more of Ni, Cr, Al and Fe. The conductive component of one embodiment of the present invention has excellent corrosion resistance and heat resistance. When used in a solid oxide fuel cell, the increase in resistance is suppressed. Therefore, the reduction in output performance of a solid oxide fuel cell having a conductive component can be suppressed and has excellent output performance.
[0042]
[12] A solid oxide fuel cell according to one embodiment of the present invention includes the conductive member described in [1] to
[11] above. Thus, the solid oxide fuel cell according to one embodiment of the present invention can have excellent output performance.
[0043]
[13] In the above
[12] , the first main surface may be in contact with at least one of a first connector and a second connector described below. Thus, the solid oxide fuel cell according to one embodiment of the present invention can have excellent output performance.
[0044] [Details of the embodiments of the present invention]
[0045] Below, refer to the attached Figure 1 A specific example of a conductive member according to an embodiment of the present invention (hereinafter also referred to as "this embodiment") and a solid oxide fuel cell having the same is described. In the drawings of the present invention, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.
[0046] In this specification, when a compound (alloy) is represented by a chemical formula that does not limit the composition ratio of the constituent elements, such as "NiCrAl", the chemical formula includes all the composition ratios (element ratios) known in the past. Furthermore, the above chemical formula includes not only the stoichiometric composition but also the non-stoichiometric composition. For example, the chemical formula of "NiCrAl" includes not only the stoichiometric composition "Ni 1 Cr 1 Al 1 ”, and also includes, for example, “Ni 1 Cr 1 Al 0.8 " This is a non-stoichiometric composition. The same is true for compounds other than "NiCrAl".
[0047] [Embodiment 1: Conductive member]
[0048] use Figure 1 to Figure 4 A conductive member according to one embodiment of the present invention will be described.
[0049] A conductive component 3 of one embodiment of the present invention (hereinafter also referred to as "this embodiment") has a porous body 10, and the porous body 10 has a skeleton 11 with a three-dimensional network structure. The shape of the porous body 10 is a plate having a first main surface 1 and a second main surface 2 opposite to the first main surface 1, and the first main surface 1 contains carbon atoms. The porous body 10 is a NiCrAl metal porous body or a NiCrAlFe metal porous body.
[0050] <<Porous body>>
[0051] <Shape of porous body>
[0052] The conductive member 3 of the present invention has a porous body 10, and the porous body 10 has a skeleton 11 of a three-dimensional network structure. In the present invention, the three-dimensional network structure can be made into the same structure as the structure described in paragraphs 0047 to 0054 of the specification of International Publication No. 2019 / 244480. In the present invention, the skeleton can be made into the same structure as the structure described in paragraphs 0034 to 0036 of the specification of International Publication No. 2019 / 244480. For example, Figure 2 and Figure 4 As shown, the porous body 10 has a three-dimensional network structure, and the three-dimensional network structure has a skeleton 11 and a pore portion 14. The skeleton 11 is composed of a skeleton body 15 and a hollow interior 13 surrounded by the skeleton body 15. The conductive member 3 of the present invention is composed of the porous body 10, and the porous body 10 has a skeleton 11 of a three-dimensional network structure.
[0053] The skeleton 11 has a hollow cylindrical portion with an interior 13 surrounded by a skeleton body 15. The cross section perpendicular to the extension direction of the cylinder can be triangular or other polygonal, or can also be circular. The skeleton 11 is cylindrical, and thus has an inner side 22 of the cylinder and an outer side 21 of the cylinder ( Figure 4 ). As for the skeleton 11, by making the interior 13 surrounded by the skeleton body 15 hollow, the porous body 10 can be made very light (that is, the conductive member 3 can be made very light). However, the skeleton 11 is not limited to being hollow, and can also be solid. In this case, the strength of the conductive member 3 can be improved.
[0054] The shape of the porous body 10 is a plate having a first main surface 1 and a second main surface 2 opposite to the first main surface 1. The thickness of the porous body 10 can be greater than 0.2 mm and less than 2 mm. By making the thickness of the porous body 10 less than 2 mm, a porous body 10 thinner than before can be formed to reduce the required amount of metal. By making the thickness of the porous body 10 greater than 0.2 mm, it can have the required strength. The thickness of the porous body 10 can also be greater than 0.5 mm and less than 1 mm. The thickness of the porous body 10 can be measured by, for example, a commercially available digital thickness gauge (TECLOCK Co., Ltd.).
[0055] <Composition of porous body>
[0056] By making the first main surface 1 contain carbon atoms, conductivity can be imparted to the first main surface 1. When the solid oxide fuel cell 150 is operating, the oxides (nickel oxide, chromium oxide, aluminum oxide, iron oxide, NiCrAl oxide, NiCrAlFe oxide, etc.) generated on the first main surface 1 increase the contact resistance between the first main surface 1 side of the conductive member 3 and the connecting member (connector), but due to the conductivity of the carbon atoms contained in the first main surface 1, the increase in the above-mentioned contact resistance is suppressed. Here, "the first main surface 1 contains carbon atoms" can also be understood as "at least a part of the carbon atoms contained in the porous body 10 are exposed and exist on the first main surface 1".
[0057] Carbon atoms may also exist in the form of conductive carbon. Thus, the conductivity of the first main surface 1 is improved, and in the solid oxide fuel cell 150, the increase in the contact resistance between the conductive member 3 and the connecting member can be further suppressed. As conductive carbon, for example, carbon black (thermal black, furnace black, lamp black, channel black, acetylene black, etc.) can be cited.
[0058] “The first main surface 1 contains carbon atoms” can be determined by the following method.
[0059] First, the outer surface of the skeleton 11 was analyzed using an Auger electron spectroscopy device (trade name "PHI 650" manufactured by PerkinElmer) in a 1 μm×1 μm rectangular measurement area at any position on the first main surface 1. The surface analysis was performed under the following conditions in accordance with JIS K0146:2002 (ISO 14606:2000).
[0060] <Measurement conditions>
[0061] Electron energy: 10kV
[0062] Electron beam current: 3mA
[0063] Angle of incidence relative to the first main surface 1: 90°
[0064] (Detector: 55°)
[0065] Beam diameter: 1nm
[0066] Mode: Surface Analysis
[0067] Elements to be measured: Metal components such as nickel, chromium, aluminum, and iron; oxygen; carbon
[0068] The same analysis was performed on any other nine positions on the first main surface 1. When carbon atoms were detected at at least one position among a total of ten positions, it was recorded as "the first main surface 1 contains carbon atoms". In addition, as long as the measurement was performed by the above method on the same conductive member 3, it was confirmed that there was no deviation in the measurement result even if the measurement position was changed arbitrarily.
[0069] In addition, as long as "the first main surface 1 contains carbon atoms", the second main surface 2 may or may not contain carbon atoms. "The second main surface 2 contains carbon atoms" can be determined by the same method as the method of determining "the first main surface 1 contains carbon atoms", except that "the second main surface 2" is the object of measurement.
[0070] The surface (outer side surface 21) of skeleton 11 is located in the region sandwiched between first principal surface 1 and second principal surface 2. If first principal surface 1 contains carbon atoms, the surface (outer side surface 21) of skeleton 11 not constituting first principal surface 1 may or may not contain carbon atoms.
[0071] <First Area>
[0072] The skeleton 11 has a first region 12, which is a region from the first main surface 1 to a plane parallel to the first main surface 1, that is, a region where the distance from the first main surface 1 to the above plane is 10 nm ( Figure 3 ).
[0073] (Composition of the first region)
[0074] The content C1 of carbon atoms in the first region 12 can be greater than 10 atm% and less than 90 atm%. Thus, when the first main surface 1 is in contact with the connecting member, the contact resistance between the conductive member 3 and the contact member can be suppressed to a lower level. In addition, by setting the upper limit of C1 to less than 90 atm%, it is possible to suppress the carbon on the surface of the skeleton from detaching and blocking the flow paths of various gases in the solid oxide fuel cell. The lower limit of C1 can be greater than 20 atm%, or greater than 25 atm%. In addition, it can also be greater than 30 atm%. The upper limit of C1 can be less than 80 atm%, or less than 70 atm%, or less than 60 atm%. C1 can be greater than 20 atm% and less than 80 atm%, or greater than 25 atm% and less than 70 atm%, or greater than 30 atm% and less than 60 atm%. The contact resistance between the conductive member 3 and the contact member can be further suppressed to a lower level.
[0075] The content of carbon atoms in the first region 12 can be measured using an Auger electron spectrometer. The surface of the skeleton 11 is used as the starting point, and the measurement is performed at positions at intervals of 1 nm in the depth direction of the skeleton 11. In addition, the depth direction refers to the direction perpendicular to the first main surface 1. That is, a total of 11 points are measured at intervals of 1 nm from 0 nm to 10 nm from the surface of the skeleton 11. The measurement is performed under the following conditions in accordance with JIS K0146:2002 (ISO 14606:2000).
[0076] <Measurement conditions>
[0077] Electron energy: 10kV
[0078] Electron beam current: 3mA
[0079] Angle of incidence relative to the first main surface 1: 90°
[0080] (Detector: 55°)
[0081] Beam diameter: 1nm
[0082] Sputtering ions: Ar
[0083] Mode: Depth Direction Analysis (Depth Profiling)
[0084] Elements to be measured: Metal components such as nickel, chromium, aluminum, and iron; oxygen; carbon
[0085] By calculating the average value of the total content of carbon atoms at each position relative to carbon atoms, metal atoms (nickel atoms, chromium atoms, aluminum atoms, iron atoms, etc.), and oxygen atoms, the average value of the content of carbon atoms in the depth direction at any position on the first main surface 1 is obtained. Furthermore, the same analysis is performed on any other four positions on the first main surface 1. C1 is obtained by calculating the average value of the content of carbon atoms at a total of five positions.
[0086] As long as the measurement is performed by the above method on the same conductive member 3, it has been confirmed that there is no variation in the measurement result even if the measurement region is arbitrarily changed.
[0087] <Types of porous bodies>
[0088] (porous metal body)
[0089] The porous body 10 is a NiCrAl metal porous body or a NiCrAlFe metal porous body. Thus, the conductivity of the conductive component 3 can be improved. Therefore, the solid oxide fuel cell 150 including the conductive component 3 can have excellent output performance. Here, the NiCrAl metal porous body refers to a porous body 10 in which the main body of the skeleton 11 contains Ni elements, Cr elements and Al elements as main components and does not contain Fe elements, and the NiCrAlFe metal porous body refers to a porous body 10 in which the main body of the skeleton 11 contains Ni elements, Cr elements, Al elements and Fe elements as main components. Here, "the main body of the skeleton 11 contains Ni elements, Cr elements and Al elements as main components" means that in the main body of the skeleton 11, the total content of Ni elements, Cr elements and Al elements is greater than 50% by mass. In addition, here, "the main body of the skeleton 11 contains Ni elements, Cr elements, Al elements and Fe elements as main components" means that in the main body of the skeleton 11, the total content of Ni elements, Cr elements, Al elements and Fe elements is greater than 50% by mass. In addition, "the main body of the skeleton 11 contains Ni element, Cr element and Al element as main components" and "the main body of the skeleton 11 contains Ni element, Cr element, Al element and Fe element as main components" are determined by adding "the content rate of each metal element in the main body of the skeleton 11" calculated by the method described later. Hereinafter, NiCrAl metal porous body and NiCrAlFe metal porous body are also collectively referred to as "metal porous body" or "porous body".
[0090] In the NiCrAl metal porous body, the main body of the skeleton 11 may include a total of more than 55% by mass of Ni, Cr and Al elements, or more than 60% by mass, or more than 65% by mass. As a result, the corrosion resistance and heat resistance of the porous body 10 are improved, and the reduction in conductivity during use can be further suppressed. In the NiCrAl metal porous body, the main body of the skeleton 11 may include a total of less than 100% by mass of Ni, Cr and Al elements, or less than 99% by mass, or less than 98% by mass. In the NiCrAl metal porous body, the main body of the skeleton 11 may include a total of more than 55% by mass and less than 100% by mass of Ni, Cr and Al elements, or more than 60% by mass and less than 99% by mass, or more than 65% by mass and less than 98% by mass.
[0091] In the NiCrAlFe metal porous body, the main body of the skeleton 11 may include a total of more than 55% by mass of Ni, Cr, Al and Fe elements, or more than 60% by mass, or more than 65% by mass. As a result, the corrosion resistance and heat resistance of the porous body 10 are improved, and the reduction in conductivity during use can be further suppressed. In the NiCrAlFe metal porous body, the main body of the skeleton 11 may include a total of less than 100% by mass of Ni, Cr, Al and Fe elements, or less than 99% by mass, or less than 98% by mass. In the NiCrAlFe metal porous body, the main body of the skeleton 11 may include a total of more than 55% by mass and less than 100% by mass of Ni, Cr, Al and Fe elements, or more than 60% by mass and less than 99% by mass, or more than 65% by mass and less than 98% by mass.
[0092] As the NiCrAl metal porous body, for example, a porous body described in Patent Document 2 (Japanese Patent Application Laid-Open No. 6-29024) and a porous body described in the specification of International Publication No. 2019 / 244480 can be used, in which the composition of the skeleton is changed to NiCrAl.
[0093] As the NiCrAlFe metal porous body, a NiCrAlFe metal porous body in which the composition of the skeleton is changed to NiCrAlFe among the porous bodies described in, for example, Patent Document 2 and the porous bodies described in the specification of International Publication No. 2019 / 244480 can be used.
[0094] The content of each metal element and oxygen in the main body of the skeleton 11 can be calculated according to the following steps. First, determine the portion where the skeleton 11 extends, and obtain an electron microscope (SEM) observation image of a cross section perpendicular to the extension direction of the skeleton 11. Next, use an EDX device attached to the SEM for analysis. As an SEM, for example, a SEM with the trade name "SUPRA35VP" manufactured by Carl Zeiss Microscopy GmbH is used. As an EDX device, for example, an EDX device with the trade name "Octane super" manufactured by Ametek, Inc. is used. Based on the atomic concentration of each element detected by the EDX device, the mass % and mass ratio of oxygen and each metal element in the skeleton main body 15 can be calculated respectively.
[0095] As long as the measurement is performed on the same skeleton 11 by the above-mentioned method, it has been confirmed that there is no deviation in the measurement result even if the measurement region is arbitrarily changed.
[0096] As long as the effects of the conductive component 3 of the present invention are not affected, the main body of the skeleton 11 can contain other elements as constituent elements. The main body of the skeleton 11 may also contain, for example, silicon, magnesium, carbon, sodium, tungsten, titanium, phosphorus, boron, silver, gold, molybdenum, nitrogen, sulfur, fluorine or chlorine as other elements. These components are sometimes included as unavoidable impurities that are inevitably mixed in the manufacturing method described later. In the skeleton 11, the content of other elements is preferably less than 5% by mass when they are counted individually, or less than 1% by mass when they are counted in total. The content of other elements in the main body of the skeleton 11 can be measured by the same method as the "content of each metal element in the main body of the skeleton 11".
[0097] As long as the measurement is performed on the same skeleton 11 by the above-mentioned method, it has been confirmed that there is no deviation in the measurement result even if the measurement region is arbitrarily changed.
[0098] <Mass per unit area of the frame>
[0099] The total mass per unit area of nickel, chromium, and aluminum in the skeleton 11 of the NiCrAl porous metal body can be 200 g / m 2 Above and 1000g / m 2 Thus, both the strength and the weight reduction of the porous body 10 can be achieved. The total mass per unit area of nickel, chromium, and aluminum can also be 250 g / m 2 Above and 900g / m 2 As a result, it is possible to further achieve both strength and weight reduction of the porous body 10. The total mass per unit area of nickel, chromium, and aluminum can be appropriately adjusted by changing the amount of slurry applied in the method for producing the NiCrAl porous metal body.
[0100] When the total mass per unit area of nickel, chromium and aluminum is converted into the mass per unit volume of the skeleton (the apparent density of the skeleton), it is as follows. That is, the "apparent density of the skeleton" can be 0.14 g / cm 3 Above and 0.75g / cm 3 Below, it can also be 0.18g / cm 3 Above and 0.65g / cm 3 Here, "the apparent density of the skeleton" is defined by the following formula.
[0101] Apparent density of skeleton [g / cm 3 ]=M[g] / V[cm 3 ]
[0102] M: mass of the skeleton [g]
[0103] V: Volume of the shape of the skeleton [cm 3 ].
[0104] The total mass per unit area of nickel, chromium, aluminum, and iron in the skeleton 11 of the NiCrAlFe metal porous body can be 200 g / m 2 Above and 1000g / m 2 Thus, both the strength and the weight reduction of the porous body 10 can be achieved. The total mass per unit area of nickel, chromium, aluminum, and iron can also be 250 g / m 2 Above and 900g / m 2 As a result, it is possible to further achieve both strength and weight reduction of the porous body 10. The total mass per unit area of nickel, chromium, aluminum, and iron can be appropriately adjusted by changing the amount of slurry applied in the method for producing the NiCrAlFe metal porous body.
[0105] When the total mass per unit area of nickel, chromium, aluminum, and iron is converted to the mass per unit volume of the skeleton (the apparent density of the skeleton), the following is obtained. That is, the "apparent density of the skeleton" can be 0.14 g / cm 3 Above and 0.75g / cm 3 Below, it can also be 0.18g / cm 3 Above and 0.65g / cm 3 the following.
[0106] <Porosity of porous body>
[0107] The porosity of the NiCrAl metal porous body and the NiCrAlFe metal porous body can be 40% or more and 98% or less, 45% or more and 98% or less, or 50% or more and 98% or less. By making the porosity of the porous body 10 40% or more, the porous body 10 can be made very light and the surface area of the porous body 10 can be increased. By making the porosity of the porous body 10 98% or less, the porous body 10 can have sufficient strength. The porosity of the porous body 10 can be appropriately adjusted by adjusting the porosity of the foaming resin used.
[0108] The porosity of the porous body 10 is defined by the following formula.
[0109] Porosity [%] = [1-{M / (V×d)}]×100
[0110] M: Mass of porous body [g]
[0111] V: Volume of the external shape of the porous body [cm 3 ]
[0112] d: Density of the metal constituting the porous body [g / cm 3 ]
[0113] <Pore diameter of porous body>
[0114] The average pore diameter of NiCrAl metal porous body and NiCrAlFe metal porous body can be greater than 60μm and less than 3500μm. By making the average pore diameter of the porous body 10 greater than 60μm, the strength of the porous body 10 can be improved. By making the average pore diameter of the porous body 10 less than 3500μm, the bendability (bending processability) of the porous body 10 can be improved. From these viewpoints, the average pore diameter of the porous body 10 can be greater than 80μm and less than 1000μm, or greater than 100μm and less than 850μm. Thus, the strength and bendability of the porous body 10 can be further improved. The average pore diameter of the porous body 10 can be appropriately adjusted by adjusting the pore diameter of the foaming resin used.
[0115] The average pore size of the porous body 10 can be calculated by the following method. First, in the porous body 10, determine the portion where the skeleton 11 extends. Cut the porous body 10 perpendicularly to the extension direction of the skeleton 11 to expose the cross section of the porous body 10. Select a cut cross section, magnify it at a magnification of 3000 times and observe it using an electron microscope to obtain an observation image. Prepare observation images of at least 10 fields of view, and calculate the number of pores per 1 inch (25.4 [mm] = 25400 [μm]) in each of the 10 fields of view. Furthermore, after taking the average value (nc) of the number of pores in the 10 fields of view, substitute it into the following formula, and use the value thus calculated as the average pore size of the porous body 10.
[0116] Average pore diameter [μm] = 25400 [μm] / nc
[0117] Here, the porosity of the skeleton 11 is the same as the porosity of the porous body 10 . In addition, the average pore diameter of the skeleton 11 is the same as the average pore diameter of the porous body 10 .
[0118] <Thickness of the frame body>
[0119] In the skeleton 11 of the NiCrAl metal porous body and the NiCrAlFe metal porous body, the thickness of the skeleton body 15 can be greater than 10 μm and less than 50 μm. Here, the "thickness of the skeleton body 15" refers to the average value of the shortest distance from the inner side surface 22 of the skeleton body 15 to the outer side surface 21 of the skeleton body 15. The thickness of the skeleton body 15 can be determined by observing the cross section of the skeleton 11 with an electron microscope. The thickness of the skeleton body 15 can be appropriately adjusted by adjusting the thickness of the foamed resin used.
[0120] The thickness of the skeleton body 15 can be specifically determined by the following method. First, in the porous body 10, determine the portion where the skeleton 11 extends. Cut the porous body 10 perpendicularly to the extension direction of the skeleton 11 to expose the cross section of the skeleton body 15. Select a cut cross section, magnify it at a magnification of 3000 times and observe it using an electron microscope to obtain an observed image. Then, in the observed image, measure the thickness of the skeleton body 15 at 10 locations. Then, calculate the average of the measured values at the 10 locations. This average is equivalent to the thickness of the skeleton body 15 of the present invention.
[0121] <<Method for producing conductive member>>
[0122] The conductive member 3 of the present embodiment can be manufactured by, for example, the following method. That is, the conductive member 3 can be manufactured by a method for manufacturing the conductive member 3 that includes the following steps in sequence:
[0123] In the first step, a plate-shaped porous body and a conductive paste in which conductive carbon particles are dispersed in a solvent are prepared;
[0124] A second step of bringing the conductive paste into contact with a porous body to obtain a conductive member precursor; and
[0125] In the third step, the conductive member 3 is obtained by heat-treating the conductive member precursor.
[0126] The first step includes: a step 1A of preparing a plate-shaped porous body; and a step 1B of preparing a conductive paste in which conductive carbon particles are dispersed in a solvent.
[0127] <1st step>
[0128] (Step 1A)
[0129] In step 1A, a first porous body composed of NiCrAl or NiCrAlFe is prepared as a plate-like porous body. The first porous body can be a commercially available porous body, a porous body described in Patent Document 2 (Japanese Patent Application Laid-Open No. 6-29024), and a porous body described in the specification of International Publication No. 2019 / 244480, in which the composition of the skeleton is changed to NiCrAl or NiCrAlFe. The first porous body composed of NiCrAl and the first porous body composed of NiCrAlFe can also be manufactured by, for example, the following method.
[0130] Regarding the manufacturing method of the first porous body composed of NiCrAl, first, Ni powder, Cr powder, Al powder (particle size is less than 100μm), solvent and binder are uniformly mixed in a specified mixing ratio to make a slurry. Solvents include water, ethanol, methanol, N-methyl-2-pyrrolidone (NMP), etc., but are not limited to these. Binders include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), etc., but are not limited to these. As a mixing method, a method of mixing at 400rpm for 1 hour by a rotating stand of a small ball mill manufactured by Asahi Rika Manufacturing can be cited, but is not limited to this. Next, a foaming resin is impregnated in the obtained slurry, whereby the slurry is applied to the foaming resin to obtain a first porous body precursor. Next, the first porous body precursor was heat treated at 650° C. in air for about 15 minutes, and then heat treated at 1000° C. in a hydrogen atmosphere for 3 hours to produce the first porous body. In addition, by adjusting the ratio of Ni powder, Cr powder, and Al powder, the ratio of Ni element, Cr element, and Al element contained in the first porous body can be appropriately adjusted.
[0131] The first porous body composed of NiCrAlFe can be manufactured by the same method, for example, except that the “Ni powder, Cr powder, Al powder (all with particle sizes less than 100 μm)” in the “manufacturing method of the first porous body composed of NiCrAl” is replaced by “Ni powder, Cr powder, Al powder, Fe powder (all with particle sizes less than 100 μm)”. In addition, by adjusting the ratio of Ni powder, Cr powder, Al powder, and Fe powder, the ratio of Ni element, Cr element, Al element, and Fe element contained in the first porous body can be appropriately adjusted.
[0132] (Step 1B)
[0133] In the 1B step, a conductive paste in which conductive carbon particles are dispersed in a solvent is prepared. The conductive carbon particles are the raw materials of the carbon atoms contained in the first main surface 1 of the conductive member 3. As conductive carbon particles, carbon black (thermal black, furnace black, lamp black, channel black, acetylene black, etc.) can be exemplified. As solvents, water, ethanol, methanol, etc. can be cited, for example. In the conductive paste, the conductive carbon particles can be set to more than 5 parts by mass and less than 40 parts by mass relative to 100 parts by mass of the solvent. In addition, in the conductive paste, the mass fraction of the conductive carbon particles can be appropriately adjusted in such a way that the content C1 of carbon atoms in the first region 12 is within the desired numerical range. In particular, in the second step, when the 2B step is implemented, since it is difficult to adjust the coating thickness of the conductive paste, the content C1 of carbon atoms in the first region 12 can be adjusted by appropriately adjusting the mass fraction of the conductive carbon particles in the conductive paste.
[0134] <Step 2>
[0135] Next, in the second step, the conductive paste is brought into contact with the first porous body to obtain a conductive member precursor. Specifically, for example, the conductive member precursor can be obtained by carrying out either the following step 2A or step 2B.
[0136] (Step 2A)
[0137] A conductive paste is applied to at least one surface of the first porous body. Then, the solvent is volatilized from the conductive paste. Thus, a conductive component precursor in which conductive carbon particles are carried on at least one surface of the porous body is obtained. In addition, the conductive paste may be further applied to both surfaces of the first porous body. In addition, the coating thickness of the conductive paste can be appropriately adjusted in such a way that the content C1 of carbon atoms in the first region 12 is within the desired numerical range. In addition, in the case where the conductive paste is applied only on one surface of the first porous body, the surface of the first porous body carrying the conductive carbon particles is equivalent to the first main surface 1 of the porous body.
[0138] (Step 2B)
[0139] The entire first porous body is immersed in the conductive paste so that the conductive paste is impregnated into the pores of the first porous body. Then, the solvent is volatilized from the conductive paste. Thus, a conductive member precursor is obtained in which conductive carbon particles are supported on the outer surface of the skeleton of the porous body.
[0140] <Step 3>
[0141] Next, the conductive component 3 is obtained by heat-treating the conductive component precursor. During the heat treatment, the temperature can be, for example, 600° C. or more and 800° C. or less. Thus, the conductive carbon particles in the conductive paste are closely attached to the porous body. During the heat treatment, the atmosphere can be, for example, a nitrogen atmosphere. The heat treatment time can be, for example, 10 minutes or more and 2 hours or less. The heat treatment atmosphere and the heat treatment time have an effect on the amount of conductive carbon particles attached to the porous body.
[0142] By carrying out the above steps, the conductive member 3 of the present embodiment 1 can be manufactured. That is, the conductive member 3 is a conductive member 3 having a porous body 10, the porous body 10 having a skeleton 11 of a three-dimensional network structure, the porous body 10 is in the shape of a plate having a first main surface 1 and a second main surface 2 opposite to the first main surface 1, the first main surface 1 contains carbon atoms, and the porous body 10 is a NiCrAl metal porous body or a NiCrAlFe metal porous body.
[0143] [Embodiment 2: Solid Oxide Fuel Cell Including Conductive Member]
[0144] use Figure 5 A solid oxide fuel cell 150 according to one embodiment of the present invention will be described. Figure 5 1 is a schematic cross-sectional view showing a solid oxide fuel cell 150 according to one embodiment of the present invention. Figure 5 In the embodiment, the solid oxide fuel cell 150 includes a hydrogen electrode conductive member 110, an air electrode conductive member 120, and a fuel cell unit 100. The fuel cell unit 100 is provided between the hydrogen electrode conductive member 110 and the air electrode conductive member 120. Here, the "hydrogen electrode conductive member 110" refers to a conductive member that supplies hydrogen in the fuel cell.
[0145] The "air electrode conductive member 120" refers to a conductive member that supplies a gas containing oxygen (e.g., air) in a fuel cell. In the solid oxide fuel cell 150 of the present embodiment, the air electrode conductive member 120 is composed of the conductive member 3 of the present embodiment 1. That is, the solid oxide fuel cell 150 of the present embodiment includes the conductive member 3 of the present embodiment 1. As a result, the contact resistance between the conductive member 3 and the contact member can be suppressed from increasing with use, so that a solid oxide fuel cell 150 with excellent output performance can be provided.
[0146] The fuel cell cell 100 may include an air electrode, a hydrogen electrode, an electrolyte layer disposed between the air electrode and the hydrogen electrode, and an intermediate layer (not shown) disposed between the air electrode and the hydrogen electrode to prevent the electrolyte layer from reacting with the air electrode. As the air electrode, for example, an oxide of LaSrCo (LSC) is used. As the electrolyte layer, for example, an oxide of Zr doped with Y (YSZ) is used. As the intermediate layer, for example, an oxide of Ce doped with Gd (GDC) is used. As the hydrogen electrode, for example, a mixture of YSZ and NiO is used. 2 mixture.
[0147] exist Figure 5In the solid oxide fuel cell 150, the solid oxide fuel cell 150 further has: a first connector 112 having a fuel flow path 114; and a second connector 122 having an oxidant flow path 124. The fuel flow path 114 is a flow path for supplying fuel (e.g., hydrogen) to the hydrogen electrode. The fuel flow path 114 is provided on the main surface of the first connector 112 that faces the main surface of the hydrogen electrode conductive member 110. The oxidant flow path 124 is a flow path for supplying an oxidant (e.g., oxygen) to the air electrode. The oxidant flow path 124 is provided on the main surface of the second connector 122 that faces the main surface of the air electrode conductive member 120. The first connector 112 and the second connector 122 are also electrical connecting members, and in the solid oxide fuel cell 150, the surface of the conductive member is in contact with the connecting member (connector). Due to the generation of oxides, the contact resistance between the conductive member and the connecting member (connector) becomes high, so sometimes the output of the solid oxide fuel cell is reduced. In the solid oxide fuel cell of the present invention, the first main surface of the conductive member is in contact with the connector, thereby suppressing an increase in contact resistance between the conductive member and the connector (connector), thereby suppressing a decrease in output of the solid oxide fuel cell.
[0148] <<Method for manufacturing solid oxide fuel cell including conductive member>>
[0149] The solid oxide fuel cell 150 including the conductive member 3 of the present embodiment can be manufactured by appropriately using a known method, except that the conductive member 3 of the present embodiment 1 is used in the air electrode conductive member 120. Therefore, the method for manufacturing the solid oxide fuel cell 150 including the conductive member 3 is not particularly limited, except that the conductive member 3 of the present embodiment 1 is used.
[0150] Example
[0151] Hereinafter, the present invention will be described in detail based on examples, but the present invention is not limited to the following examples.
[0152] [Example 1]
[0153] <<Manufacturing of porous body>>
[0154] In Example 1, porous bodies of Sample Nos. 1-1 to 1-11 were produced as follows.
[0155] <1st step>
[0156] In order to prepare a plate-shaped first porous body composed of NiCrAl, first, 50 parts by mass of Ni powder (particle size less than 100 μm), 14 parts by mass of Cr powder (particle size less than 100 μm), 6 parts by mass of Al powder (particle size less than 100 μm), 27 parts by mass of water (solvent) and 3 parts by mass of PVdF (binder) are mixed at 400 rpm for 1 hour by a small ball mill rotating stand manufactured by Asahi Rika Manufacturing Co., Ltd., thereby preparing a slurry. Next, a polyurethane resin (foaming resin) is impregnated in the obtained slurry, thereby applying the slurry on the foaming resin to obtain a first porous body precursor. Next, after the first porous body precursor is heat-treated at 650°C in air for about 15 minutes, it is heat-treated at 1000°C in a hydrogen atmosphere for 3 hours, thereby preparing a first porous body composed of NiCrAl (1A process).
[0157] Furthermore, acetylene black (conductive carbon particles) as a raw material containing carbon atoms was dispersed in the mass parts listed in Table 1 with respect to 100 mass parts of distilled water (solvent) to prepare a conductive paste (step 1B). In addition, in sample number 1-1, the description that distilled water (solvent) is "100 mass parts" and carbon black is "0 mass parts" means that distilled water (solvent) containing no carbon black was used.
[0158] <Step 2>
[0159] The conductive paste was applied to the first main surface of the first porous body, and the coating thickness was adjusted so that the carbon atom content C1 in the first region became the value described in Table 1. Next, the conductive paste applied to the first main surface was vacuum dried at 110° C., thereby volatilizing the distilled water (solvent) from the conductive paste. Based on the above, a conductive component precursor in which acetylene black (conductive carbon particles) was supported on the first main surface of the first porous body was obtained.
[0160] <Step 3>
[0161] Next, the conductive member precursor was heat-treated under the conditions described in Table 1 to obtain a conductive member.
[0162] [Table 1]
[0163] Table 1
[0164]
[0165] Thus, conductive members of sample numbers 1-1 to 1-11 were manufactured.
[0166] <<Evaluation of properties of conductive members>>
[0167] <Presence or absence of carbon atoms on the first principal surface>
[0168] For the conductive members of sample numbers 1-1 to 1-11, the presence or absence of carbon atoms on the first main surface was determined by the method described in Embodiment 1. The obtained results are described in the "Presence or absence of carbon atoms" column of Table 1. In addition, "Presence or absence of carbon atoms" means "the first main surface contains carbon atoms", and "Presence or absence of carbon atoms on the first main surface" means "the first main surface does not contain carbon atoms".
[0169] <Composition of the first area>
[0170] For the conductive members of sample numbers 1-1 to 1-11, the carbon atom content C1 in the first region was determined by the method described in Embodiment 1. The obtained results are described in the column “C1 [atm%]” in Table 1, respectively.
[0171] <Contact resistance>
[0172] The contact resistance of the conductive members of sample numbers 1-1 to 1-11 was evaluated by the following method.
[0173] The two interconnection simulation plates 202 are connected to a resistance measuring machine 200 (manufactured by Tsuruga Electric Co., Ltd., trademark: low resistance meter 356E) via a platinum wire 201 for conducting electricity. The conductive member 3 is sandwiched between the two interconnection simulation plates 202 ( Figure 6 ). Next, after the connector simulation plate 202 and the conductive component 3 were heated to 800°C in a thermostatic chamber, the contact resistance value was measured using a four-terminal method. Based on the obtained contact resistance value, the contact resistance was evaluated using the following four-level evaluation of B to E. Here, if the evaluation result of the contact resistance is any one of B, C, and D, it means that the contact resistance of the conductive component 3 is particularly low, and the solid oxide fuel cell can have particularly excellent output performance through the conductive component 3. The results are recorded in the "Contact Resistance" column of Table 1.
[0174] B: The contact resistance of the sample is greater than 85% and 90% or less of the contact resistance of the conductive member of sample number 1-1.
[0175] C: The contact resistance of the sample is greater than 90% and 95% or less of the contact resistance of the conductive member of sample number 1-1.
[0176] D: The contact resistance of the sample is greater than 95% and 99% or less of the contact resistance of the conductive member of sample number 1-1.
[0177] E: Benchmark.
[0178] The conductive components of sample numbers 1-2 to 1-11 correspond to the embodiments. On the other hand, the conductive component of sample number 1-1 corresponds to the comparative example. Compared with the conductive component of sample number 1-1, the conductive components of sample numbers 1-2 to 1-11 have a particularly low contact resistance. That is, compared with the solid oxide fuel cell having the conductive component of sample number 1-1, the solid oxide fuel cell having the conductive components of sample numbers 1-2 to 1-11 can have a particularly excellent output performance.
[0179] From the above, it can be seen that the solid oxide fuel cells having the conductive members of sample numbers 1-2 to 1-11 are excellent in output performance.
[0180] [Example 2]
[0181] <<Manufacturing of conductive member>>
[0182] In Example 2, conductive members of sample numbers 2-1 to 2-11 were manufactured as follows.
[0183] <1st step>
[0184] In order to prepare a plate-shaped first porous body composed of NiCrAlFe, first, 30 parts by mass of Ni powder (particle size less than 100 μm), 13 parts by mass of Cr powder (particle size less than 100 μm), 6 parts by mass of Al powder (particle size less than 100 μm), 15 parts by mass of Fe powder (particle size less than 100 μm), 33 parts by mass of water (solvent) and 3 parts by mass of PVdF (binder) are mixed at 400 rpm for 1 hour by a small ball mill rotating frame manufactured by Asahi Rika Manufacturing Co., Ltd. Then, a polyurethane resin (foaming resin) is impregnated in the obtained slurry, and the slurry is applied to the foaming resin to obtain a first porous body precursor. Then, after the first porous body precursor is heat-treated at 650°C in air for about 15 minutes, it is heat-treated at 1000°C in a hydrogen atmosphere for 3 hours to prepare a first porous body composed of NiCrAlFe (1A process).
[0185] Furthermore, acetylene black (conductive carbon particles) as a raw material containing carbon atoms is dispersed in distilled water (solvent) to prepare a conductive paste (step 1B).
[0186] <Step 2>
[0187] The conductive paste was applied to the first main surface of the first porous body, and the coating thickness was adjusted so that C1 became the value described in Table 2. Next, the conductive paste applied to the first main surface was vacuum dried at 110° C., thereby volatilizing the distilled water (solvent) from the conductive paste. Based on the above, a conductive member precursor in which acetylene black (conductive carbon particles) was supported on the first main surface of the first porous body was obtained.
[0188] <Step 3>
[0189] The conductive member precursor was heat-treated under the conditions described in Table 2 to obtain a conductive member.
[0190] [Table 2]
[0191] Table 2
[0192]
[0193] Thus, conductive members of sample numbers 2-1 to 2-11 were manufactured.
[0194] <<Evaluation of properties of conductive members>>
[0195] <Presence or absence of carbon atoms on the first principal surface>
[0196] The conductive members of Sample Nos. 2-1 to 2-11 were evaluated for the presence or absence of carbon atoms on the first main surface by the same method as in Example 1. The obtained results are described in the column “Presence or absence of carbon atoms” in Table 2.
[0197] <Composition of the first area>
[0198] For the conductive members of sample numbers 2-1 to 2-11, the composition of the first region was determined by the same method as in Example 1. The obtained results are described in the column “C1 [atm %]” in Table 2, respectively.
[0199] <Contact resistance>
[0200] For the conductive members of sample numbers 2-1 to 2-11, the contact resistance was evaluated by the same method as in Example 1 except that the contact resistance was evaluated by the following four-level evaluation of B' to E'. The obtained results are recorded in the "Contact Resistance" column of Table 2. The evaluation result of the contact resistance is any one of B', C', and D', which means that the contact resistance of the conductive member is particularly low, and the solid oxide fuel cell can have particularly excellent output performance through the conductive member.
[0201] B′: The contact resistance of the sample is greater than 85% and 90% or less of the contact resistance of the conductive member of sample number 2-1.
[0202] C′: The contact resistance of the sample is greater than 90% and 95% or less of the contact resistance of the conductive member of sample number 2-1.
[0203] D′: The contact resistance of the sample is greater than 95% and 99% or less of the contact resistance of the conductive member of sample number 2-1.
[0204] E': Benchmark.
[0205] The conductive components of sample numbers 2-2 to 2-11 correspond to the embodiments. On the other hand, the conductive component of sample number 2-1 corresponds to the comparative example. Compared with the conductive component of sample number 2-1, the conductive components of sample numbers 2-2 to 2-11 have a particularly low contact resistance. That is, compared with the solid oxide fuel cell having the conductive component of sample number 2-1, the solid oxide fuel cell having the conductive components of sample numbers 2-2 to 2-11 can have a particularly excellent output performance.
[0206] From the above, it can be seen that the solid oxide fuel cells having the conductive members of sample numbers 2-2 to 2-11 are excellent in output performance.
[0207] Although the embodiments and examples of the present invention have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples will be appropriately combined.
[0208] The embodiments disclosed this time should be considered as illustrative in all aspects and not restrictive. The scope of the present invention is shown by the claims rather than the embodiments described above, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0209] Description of Reference Numerals
[0210] 1 First main surface
[0211] 2 Second main surface
[0212] 3 Conductive components
[0213] 10 porous body
[0214] 11 Skeleton
[0215] 12. First Area
[0216] 13 Interior
[0217] 14 Stomata
[0218] 15 Skeleton body
[0219] 21 Outer side
[0220] 22 Inside side
[0221] 100 Battery cells for fuel cells
[0222] 110 Conductive member for hydrogen electrode
[0223] 112 First connector
[0224] 114 Fuel flow path
[0225] 120 Conductive member for air electrode
[0226] 122 Second connector
[0227] 124 Oxidant flow path
[0228] 150 Solid Oxide Fuel Cell
[0229] 200 Resistance measuring machine
[0230] 201 Platinum Wire
[0231] 202 Connector Simulation Board
Claims
1. A conductive member comprising a porous body, The porous body has a skeleton with a three-dimensional network structure. The porous body is in the shape of a plate having a first main surface and a second main surface opposite to the first main surface. The first main surface comprises carbon atoms, The porous body is a NiCrAl metal porous body or a NiCrAlFe metal porous body.
2. The conductive member according to claim 1, wherein The carbon atoms exist in the form of conductive carbon.
3. The conductive member according to claim 1 or 2, wherein The skeleton has a first region, The first region is a region from the first main surface to a plane parallel to the first main surface, and the distance from the first main surface to the plane is 10 nm. The content of carbon atoms in the first region is 10 atm % or more and 90 atm % or less.
4. The conductive member according to claim 3, wherein The content is 20 atm % or more and 80 atm % or less.
5. The conductive member according to claim 3, wherein The content is 30 atm % or more and 70 atm % or less.
6. The conductive member according to any one of claims 1 to 5, wherein The porous body has a thickness of 0.2 mm or more and 2 mm or less.
7. The conductive member according to any one of claims 1 to 6, wherein The porous body has an average pore diameter of 60 μm or more and 3500 μm or less.
8. The conductive member according to claim 7, wherein The porous body has an average pore diameter of 100 μm or more and 850 μm or less.
9. The conductive member according to any one of claims 1 to 8, wherein The porous body has a porosity of 50% or more and 98% or less.
10. The conductive member according to any one of claims 1 to 9, wherein In the NiCrAl porous metal body, the skeleton body contains Ni element, Cr element and Al element in a total amount of 55 mass % or more.
11. The conductive member according to any one of claims 1 to 9, wherein In the NiCrAlFe porous metal body, the skeleton body contains 55 mass % or more of Ni element, Cr element, Al element and Fe element in total. 12 . A solid oxide fuel cell comprising the conductive member according to claim 1 .
13. The solid oxide fuel cell according to claim 11, wherein: The first main surface is in contact with at least one of the first connecting body and the second connecting body.
Citation Information
Patent Citations
Solid electrolyte fuel cell
JP1994029024A
Method for estimating residual carbon production volume in heavy hydrocarbons and method for designing heavy hydrocarbons desulfurization catalyst
JP2022155329A
Metal foam stack and manufacturing method therefor
WO2016021988A1
Porous body, current collector including same, and fuel cell
WO2019244480A1